حلة الأعيان على عمدة البيان لأبي علي حسين بن علي بن طلحة الرجراجي الشوشاوي ت 899 هـ - ذهبي بوبكر الصديق (University Eloued جامعة الوادي, 2024)
إنّ مِن أهمّ المنظومات التي جمعت الكتبَ الأمّهات في الرّسم والضّبط منظومة مورد الظّمآن للخرّاز، والتي جعَلَ ذيلَها خاصًّا بعلم الضّبط القرآنيّ، وقد انبرى لشرحه عدد من العلماء، وكان لِأبي عليّ حسين بن عليّ الشوشاويّ شأوٌ في ذلك في كتابه الذي سمّاه: "حلّة الأعيان على عمدة البيان". ولأجل إخراج هذا الكتاب محقّقا جاءت هذه الرّسالة والتي عنونها: "حلّة الأعيان على عمدة البيان لأبي عليّ حسين بن عليّ بن طلحة الرجراجيّ الشوشاويّ -ت899ه- دراسةٌ وتحقيقٌ"، والتي كان إشكالها الرّئيس يتمثّل في: ما القيمة العلميّة لهذا الشّرح الكبير والموسوعة العظيمة في هذا العلم؟ واشتملت الرّسالة على قسمَيْنِ: قسم دراسةٍ، وقسم تحقيق: فأمّا قسم الدّراسة فقد جاء فيه التعريف بالخرّاز، وبنظمه، وبعلم الضّبط، ثمّ التّعريف بالرجراجيّ، ثمّ بحلّة الأعيان؛ بذكر قيمته، وأبوابه، ومصادره، ومنهج مؤلّفه فيه، ثمّ ذكرتُ نماذج من اختياراته في الكتاب. وأمّا قسم التّحقيق فقد اعتمدتُّ على خمس نسخٍ مخطوطةٍ لإخراج نصّ المؤلّف في كتابه، والذي جعله في مقدّمة وثمانية أبواب؛ فجاء بعد تحقيقه بتوفيق من اللّه مشكولًا، معزوَّ النّصوص، وحشّيتُ بتعليقات وتتميمات في الذي رأيتُه جديرًا أن يُذكر ولا يُـمكن الاستغناء عنه، خاصّة في ما تعلّق بعلم الضّبط الذي هو لبّ الكتاب. وإنّ من أهمّ النتائج المتوصَّل إليها بعد تحقيق الكتاب أنّ حلّةَ الأعيان جلَّتْ عنِ الوصْفِ؛ في جمْعِ نصوص أئمّة هذا الشأن، وبيان الأشهر والأظهر من الأقوال، وبيان لصور الضّبط، بأسلوب سهلٍ واضح، ومن النتائج كذلك أثريّة صاحبها في العلم؛ فهو لا يعدو أقوال أشياخ الضّبط: أبي عمرو الدّانيّ، وأبي داود سليمان بن نجاح، وأبي إسحاق التُّجيبيّ؛ وإذا جَوَّزَ غيْرَ ما ذكروه فإنّـما يجوّزُه على قياس صحيحٍ ومَـحْمَلٍ على نصوصهم وقواعدهم في هذا العلم. ومن أهمّ التوصيات جمعُ الأقوال المشهورة في الضّبط خاصّةً ما اتّفق عليه أشياخ الضّبط الثّلاثة أبي عمرو وأبي داود والتّجيبيّ لأنّ هذا العلم بُني على أقوالهم، وحلّة الأعيان احتوت على طائفة كبيرة من ذلك يصرّح فيها الرّجراجيّ بالشّهرة أو باتفاق الثّلاثة. One of the most important poems that collected the principal books in Koran writing and vowelization is Mawrid Al-Dham'an poem of Alkharaz. He made the last of it specific to the Koran vowelization science, and a number of scholars have explained it. Abu Ali Hussein bin Ali Al-Shawshawy had precedence in this in his book, which he called: “Hollat Al-Ayan ala Umdat Al-Bayan.” This thesis came to produce this book verified, and which was titled: “Hollat Al-Ayan Ala Umdat Al-Bayan by Abu Ali Hussein bin Ali bin Talha Al-Ragragui Al-Shawshawi -d. 899 A.H - study and verification.” Its main problem was to know the scientific value of this big explanation and the great encyclopedia in this science. It included two parts: a study section and a verification section. The study section includes the identification of Al-Kharaz, his poem, the vowelization science, the identification of Al-Rajraji, then Hollat Al'aeyane by mentioning its value, its chapters, its sources, and its author’s approach to it, and then I mentioned examples of his choices in the book. In the verification section, I relied on five manuscript copies to produce the author's text in his book, which he included in an introduction and eight chapters. It came after its verification with the grace of God vowelized, ascribed texts, and I annotated with comments and complements in what I saw worthy of mentioning and indispensable especially with regard to the vowelization science which is the core of the book. One of the most important results reached after the verification of the book is that Hollat Al-Ayan is exceeding all description in collecting the texts of the imams in this matter, explaining the most famous and most obvious sayings and clarifying the vowelization images in an easy and clear manner. Among the results is also the antiquity of its owner in science. He does not go beyond the sayings of the sheikhs of vowelization science: Abu Amr Al-Dani, Abu Dawud Suleiman bin Najah and Abu Ishaq Al-Tujibi. If he permitted other than what they mentioned, he permitted it according to a correct analogy and it is based on their texts and rules in this science. Among the most important recommendations is the collection of well-known sayings in the vowelization science, especially what was agreed upon by the three sheikhs of the vowelization science, Abi Amr, Abi Dawud, and Al-Tujibi because this knowledge was built on their sayings. Hollat Al-Ayan contained a large number of that, in which Al-Rajraji declares the fame or the agreement of the three.
دراسة وتحقيق
أطروحة دكتوراه
Keywords: الهمزة; التسهيل; الضبط; مواضع; صورة